Digital innovation for optimization of hospital administration - Habeahan, Immanuel; Paramarta, Vip; Kosasih; Fitriana (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2025)
This community service program aims to improve hospital administrative efficiency through training and mentoring in service digitalization. The program began with an initial visit to obtain permission and understand the hospital’s needs, followed by a three-day training session involving 16 participants from the social media, public relations, and administrative teams. The training covered the use of Electronic Medical Records (EMR), digital queue systems, online scheduling, and digital marketing strategies through SEO and SEA. Evaluation results showed a significant improvement in hospital staff’s digital literacy, with the median pre-test score of 40 increasing to 80 in the post-test (p=0.000), demonstrating a substantial enhancement in digital literacy. This improvement positively impacted administrative processes, making them faster and more organized. Additionally, digital marketing optimization increased patient engagement with hospital services through online searches. To ensure the program's long-term benefits, an internal team was established to oversee continuous monitoring and evaluation. This program proves that digitalizing hospital administration can enhance operational effectiveness and provide a better service experience for patients.